Endoscopic foreign body retrieval from the caecum – A case report and push for intervention guidelines. (January 2022) - Apikotoa, Sharie; Ballal, Helen; Wijesuriya, Ruwan
Abstract: Introduction and importance: Endoscopic foreign body retrieval in the upper gastrointestinal tract is well established, however indications for endoscopy for retained foreign bodies in the lower gastrointestinal tract and specifically the right colon is still being navigated [3]. A PubMed and Google Scholar search discovered a variety of case reports detailing various methods and indications for endoscopic retrieval of right sided colonic foreign bodies. This case report endeavors to supplement the literature so that guidelines can one day be established for colonoscopic retrieval of right-sided foreign bodies. Case presentation: 36-year-old male prisoner swallowed 6.5 cm nail clippers with a long-standing history of intentional foreign body ingestion (FBI) including multiple laparotomies for foreign body retrievals. Computerized tomography (CT) was used initially to confirm the position of the nail clippers. After almost two weeks of failure of the foreign body (FB) to move beyond the caecum as demonstrated on plain abdominal X-rays, the patient had a colonoscopy with successful retrieval of the FB. Clinical discussion: This case report hopes to encourage the consideration of colonoscopy for retrieval of right sided colonic foreign bodies that have failed to pass on their own and where an operation may come with increased risk (multiple laparotomies, multiple comorbidities, and higher anaesthetic risk for a general anaesthetic). Colonoscopy/endoscopy still has inherent risk and this patient did have an episode of temporary laryngospasm that required intubation and monitoring in the intensive care unit post operatively. Despite this the patient recovered and was discharged day one post procedure without further complication. The case report has been reported in line with the SCARE 2020 criteria (Agha et al., 2020 [2] ). Conclusion: Indications for consideration of endoscopic retrieval of foreign bodies in the right colon have not been entirely detailed as endoscopy is for upper gastrointestinal foreign bodies. This case report documents the indications for endoscopy in the clinical context of a recurrent FBI and a history of multiple laparotomies with failure of the FB to move beyond the caecum. Highlights: Foreign body ingestion is common, but rate of intervention is low. Endoscopic intervention of upper gastrointestinal tract foreign bodies is well established. There are no established guidelines for endoscopic retrieval of caecal foreign bodies. Colonoscopy should be considered in those without immediate complication.